2011
DOI: 10.1111/j.1365-2710.2011.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of three most widely used analgesics in six European countries

Abstract: Effective therapy needs good prescribing and well-informed prescribers and patients. Our study highlights wide differences in analgesic consumption even among similar European countries. The basis of these differences and their potential clinical impact require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 8 publications
(12 reference statements)
4
20
0
Order By: Relevance
“…Paracetamol is one of the most frequently used analgesics in Europe , and we showed that the sales of paracetamol have increased in all Nordic countries. The sales of paracetamol have previously been reported to increase from 2003 to 2009 in Denmark, Norway and Finland . We showed that this trend continued through 2015.…”
Section: Discussionsupporting
confidence: 63%
“…Paracetamol is one of the most frequently used analgesics in Europe , and we showed that the sales of paracetamol have increased in all Nordic countries. The sales of paracetamol have previously been reported to increase from 2003 to 2009 in Denmark, Norway and Finland . We showed that this trend continued through 2015.…”
Section: Discussionsupporting
confidence: 63%
“…Sales of analgesics have risen steadily over the past 20 years in Europe [9][10][11][12]. Indeed, in France, analgesics were the most used therapeutic class within primary care settings in 2013 (22% of the market share for all medications) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of NSAIDs as painkillers has positioned them among the most consumed non-prescription drugs in the market [3,58]. Lipids are characterized by a sharp phase transition temperature that depends on the length of the alkyl chains [55] and the type of polar head groups [56].…”
Section: Discussionmentioning
confidence: 99%